Conventional breeding approach for obtaining ornamentally superior F1 hybrids of periwinkle (Catharanthus roseus L.) - SINGH, MANINDERPAL; DHATT, K K (Journal of Ornamental Horticulture, 2025)
Periwinkle is an herbaceous plant mostly known for its medicinal values. Its use as a flowering plant is limited but it has potential for being important summer and rainy season flowering annual in tropical and sub tropical areas. Keeping this in mind, eight inbred lines of distinct plant characters and flower colours (Magenta with white centre, Magenta, Cherry pink, Peach, Purple, Pink with dark pink centre, Light pink with white centre and White with red spot) were crossed in half-diallel to obtain twenty eight F1 hybrids. These hybrids along with the parents were evaluated for growth and flowering parameters. The results revealed the superiority of F1 hybrids in terms of their earliness to flowering, longer flowering duration and greater number of flowers per plant. The values of phenotypic and genotypic coefficients of variation were high (>20%) for number of flowers per plant and follicle length. Traits like plant height, plant spread, leaf width, leaf length, petiole length, flower diameter and corolla tube length were highly heritable. Moderate to high heritability along with greater genetic advance was recorded in traits viz. plant height, plant spread, number of branches per plant, petiole length, number of flowers per plant and follicle length. These results can be helpful in selection of superior cross combinations and development of improved genotypes in periwinkle for its use as potential ornamental crop.